ISLAMIC BANKS AND REGULATORY ADAPTATION: IMPLEMENTATION OF SHARIA-COMPLIANT BANKING SERVICES IN THE EUROPEAN UNION - A. A. Yo‘ldoshbekov (Modern American Journals, 2025)
This article analyzes the regulatory adaptation and practical implementation of Islamic banking services in the European Union. The study examines how Western financial centres — particularly the United Kingdom, France, Germany, Luxembourg, and Ireland — have incorporated Sharia-compliant financial instruments into their national financial systems. The paper highlights the mechanisms used to legalize Islamic banking operations: tax neutrality, licensing reforms, introduction of sukuk markets, and the establishment of “Islamic windows” within conventional banks. The results show that integration is driven by two major factors: (1) increasing Muslim population and demand for Islamic financial products, and (2) economic interest of European capital in attracting investments from GCC countries. The article concludes that Islamic banking in Europe has shifted from being a religious alternative to becoming part of competitive financial market infrastructure.
Keywords: Islamic banking, Sharia-compliant finance, regulatory adaptation, sukuk, Islamic windows, European Union, financial regulation.